(untitled) (Third Sector Social Economic Review, 2025)
This study investigates Philip Pettit’s reconceptualization of freedom as non-domination within the context of republican political philosophy. The primary objective is to demonstrate that, unlike the modern dichotomy of negative and positive freedom, Pettit’s concept represents a status defined not only by the absence of interference but also by the institutional limitation of arbitrary power. A secondary aim is to investigate the possibility of its practical realization. The study analyzes Pettit’s theory across philosophical, conceptual, normative, and critical dimensions, grounding the discussion in the historical roots of the republican tradition. Adopting a qualitative philosophical analysis approach, the research examines the structural conditions of freedom, domination, and arbitrariness through text-based analysis and conceptual comparisons. Applying Pettit’s dual-channel democracy model, the study assesses how freedom is secured through institutional safeguards and discusses the model’s limitations in light of liberal, communitarian, Marxist, and feminist critiques. Ultimately, the study demonstrates that non-domination is a condition that must be conceived not only as a legal but also as a social and ethical process, arguing that freedom can only be sustained through accountable institutions, transparent governance, and effective citizen participation. Pettit’s approach offers a dynamic normative framework that reorients freedom from individual autonomy toward social reciprocity.